1989
DOI: 10.1128/aac.33.5.646
|View full text |Cite
|
Sign up to set email alerts
|

Failure of zinc gluconate in treatment of acute upper respiratory tract infections

Abstract: Zinc is a trace metal with in vitro activity against rhinovirus, the major etiologic agent in acute upper respiratory tract infections (URIs). A previous trial of zinc gluconate supported its efficacy in treating URIs, but the effectiveness of blinding was uncertain. We conducted a prospective randomized trial of zinc gluconate versus a taste-matched placebo of sucrose octaacetate. Lozenges containing either 23 mg of elemental zinc or placebo were taken every 2 h. Eleven URI symptoms were rated daily on a scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 8 publications
0
75
0
Order By: Relevance
“…The method of randomization was not reported in two trials. 28,38 The remaining six trials had low risk of bias. Sensitivity analysis excluding the trials with high risk of bias did not change the results, so the evidence was not downgraded.…”
Section: E556mentioning
confidence: 99%
See 2 more Smart Citations
“…The method of randomization was not reported in two trials. 28,38 The remaining six trials had low risk of bias. Sensitivity analysis excluding the trials with high risk of bias did not change the results, so the evidence was not downgraded.…”
Section: E556mentioning
confidence: 99%
“…The remaining four trials either measured but did not report the outcome 26,29 or reported the proportion of symptomatic patients on each day. 38,39 Eight trials (n = 934) could be pooled in the meta-analysis ( Figure 2). All trials involved patients with naturally acquired colds.…”
Section: Duration Of Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts made to duplicate the success which Eby et al 1 had in 1984 in reducing the duration of the common cold using zinc gluconate have generally been disappointing, [2][3][4] the probable reason being that zinc gluconate was inactivated by additives used to mask its unpleasant taste. It has been demonstrated that of these agents, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that of these agents, e.g. citric acid, 2 tartaric acid, 3 or mannitol/sorbitol, 4 inactivate zinc by chelation in saliva. 5,6 Unflavoured zinc gluconate and the zinc gluconate -glycine (ZGG) lozenges used in the present study release 90 -93% of zinc ions, 6 whereas citric acid 2 and mannitol/sorbitol 4 formulations release no zinc ions when dissolved in the mouth.…”
Section: Introductionmentioning
confidence: 99%